Deacetylated SNAP47 recruits HOPS to facilitate autophagosome-lysosome fusion independent of STX17 - Fenglei Jian; Shen Wang; Wenmin Tian; Yang Chen; Shixuan Wang; Yan Li; Cong Ma; Yueguang Rong (Nature Communications)
Abstract Autophagy, a conserved catabolic process implicated in a diverse array of human diseases, requires efficient fusion between autophagosomes and lysosomes to function effectively. Recently, SNAP47 has been identified as a key component of the dual-purpose SNARE complex mediating autophagosome-lysosome fusion in both bulk and selective autophagy. However, the spatiotemporal regulatory mechanisms of this SNARE complex remain unknown. In this study, we found that SNAP47 undergoes acetylation followed by deacetylation during bulk autophagy and mitophagy. The acetylation status of SNAP47 is regulated by the acetyltransferase CBP and the deacetylase HDAC2. Notably, the spatiotemporal regulatory dynamics of SNAP47 acetylation differ between bulk autophagy and mitophagy due to distinct regulation on the activity of acetyltransferase and deacetylase. Acetylated SNAP47 inhibits autophagosome-lysosome fusion by indirectly impeding SNARE complex assembly. Mechanistically, deacetylated SNAP47 recruits HOPS components to autophagic vacuoles independently of STX17 and STX17-SNAP47 interaction, while acetylated SNAP47 inhibits this recruitment, consequently leading to the failure of SNARE complex assembly. Taken together, our study uncovers a SNAP47 acetylation-dependent regulatory mechanism governing autophagosome-lysosome fusion by modulating the recruitment of HOPS to autophagic vacuoles without involving STX17, SNAP47-STX17 interaction and ternary SNARE complex formation.